An appraisal of vessel-source pollution for Malaysian legal framework / Nur Irinah Mohamad Sirat, Syatirah Abu Bakar, Mohd Zulhelmey Abdullah - Mohamad Sirat, Nur Irinah; Abu Bakar, Syatirah; Abdullah, Mohd Zulhelmey (Institute of Research Management & Innovation (IRMI), 2012)
The Deepwater Horizon oil spill in the Gulf of Mexico is one of the largest accidental marine oil spills in the history of the petroleum industry. It has raised serious concerns about marine oil pollution particularly on the ecological disturbances of the marine environment. Vessel-source pollution is one of the the major sources of oil pollution that harm the coastal marine environment in Malaysia. The strategic location of this country has made it as one of the busiest shipping route in the world due to the huge petroleum demand from the Middle East to the Far East. Petroleum tankers and petroleum run merchant vessels that used our coastal waters as the thoroughfare between the West and the East have continuously exposed the Malaysian waters to the problem of vessel source pollution, particularly oil pollution. This matter contributes quite significantly towards the ecological disturbances of the marine environment as the western coastal area of Malaysia is extremely sensitive to oil spill hazards when most of the area is covered by mangrove forests. The vulnerability of the coastal area was exposed by the recent incident of oil spill washed up onto a 600m coastal stretch located at the Tanjung Piai National Park, Johor and the oil spill was believed to have occurred when the vessels passing by were conducting illegal oil dumping or oil transferring activities. ln the light of this set up, this research, thus, will critically analyse the present state of the laws in relation to vessel-source pollution in Malaysia as set against the landscape of the international conventions to gauge whether appropriate responses have been made by the Malaysian legislations in view of Malaysian obligations under the relevant international conventions and to propose necessary changes accordingly. This study is based on a qualitative research. References will also be made to our local statutes as well as the relevant international conventions. The expected outcome of this research may form the basis for policy maker’s consideration in formulating a legislation that specifically addresses the matter.